2019
DOI: 10.21203/rs.2.17412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeny of teleost connexins reveals highly inconsistent intra- and interspecies use of nomenclature and misassemblies in recent teleost chromosome assemblies

Abstract: Background: Based on an initial collecting of database sequences from the gap junction protein gene family (also called connexin genes) in a few teleosts, the naming of these sequences appeared variable. The reasons could be (i) that the structure in this family is variable across teleosts, or (ii) unfortunate naming. Rather clear rules for the naming of genes in fish and mammals have been outlined by nomenclature committees, including the naming of orthologous and ohnologous genes. We therefore analyzed the c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…1, 2). Across the family of connexin genes there are seven human connexins for which zebrafish only has a single homolog, eight human connexins for which zebrafish has two homologs, two zebrafish connexins that have no direct homolog but share sequence similarity to human connexins, and sixteen zebrafish connexins that are not present in humans but are conserved in other teleost and mammalian lineages 30 . We summarize these relationships in Table 1, listing zebrafish connexin genes and their closest relationship with their human counterparts, providing known human and zebrafish expression patterns and phenotypes for comparison.…”
Section: Zebrafish Have 41 Connexin Genesmentioning
confidence: 99%
See 2 more Smart Citations
“…1, 2). Across the family of connexin genes there are seven human connexins for which zebrafish only has a single homolog, eight human connexins for which zebrafish has two homologs, two zebrafish connexins that have no direct homolog but share sequence similarity to human connexins, and sixteen zebrafish connexins that are not present in humans but are conserved in other teleost and mammalian lineages 30 . We summarize these relationships in Table 1, listing zebrafish connexin genes and their closest relationship with their human counterparts, providing known human and zebrafish expression patterns and phenotypes for comparison.…”
Section: Zebrafish Have 41 Connexin Genesmentioning
confidence: 99%
“…There are a limited number of rows where the zebrafish connexin gene resembles its human counterpart(s), but the genes are not direct homologs. For example, the human GJB2/GJB6 genes are duplicated in the human lineage while having only a single similar gene in zebrafish called gjb8 30 . Despite not being direct homologs, expression and mutant analyses have found that zebrafish gjb8 and human GJB2/GJB6 genes are all involved in inner-ear support cell function and loss of these genes in their respective systems causes deafness 20,52,53 .…”
Section: Zebrafish Have 41 Connexin Genesmentioning
confidence: 99%
See 1 more Smart Citation